NOTES ON THE DISTRIBUTION OF INVASIVE FRESHWATER SNAIL POMACEA CANALICULATA (LAMARCK, 1822) AND P. INSULARUM ( D'ORBIGNY, 1835) IN INDONESIA - RISTIYANTI M. MARWOTO; NUR R. ISNANINGSIH NUR (BIOTROPIA, 2011)
The freshwater snails and have been reported as importantinvasive species causing damage to crops and predominantly wetland rice in Asia. These snailsare known as â€œGolden Apple Snailâ€ (GAS), an introduced species from Argentina.or known as â€œkeong mas, keongmurbeiâ€ was introduced in Indonesia around 1983,and after more than 20 years, it now can be found very abundant at various habitats such asmarshes, ponds, irrigations, lakes and rice fields in almost all places in Indonesia.Based on the collections of these snails deposited in the MZB (Museum ZoologicumBogoriense, Research Center for Biology) and secondary data (references), the distributionof these two snails was studied. is widely distributed, while only found at Lake Semayang and Lake Balikpapan in Kalimantan. The distribution map ispresented and will be useful as a basic information to manage these invasive snails.